Pengaruh Budaya Kerja dan Retensi Terhadap Kinerja Karyawan Gen Z pada Abuya Group - Dean Izzat, Muhammad; Hasanah, Hasanah (Economic Reviews Journal, 2026)
This study aims to analyze the influence of work culture and employee retention on the performance of Generation Z employees at Abuya Group. The demographic shift in the workforce dominated by Generation Z requires organizations to adjust their human resource management strategies. This research employs a quantitative method with an associative approach involving 45 Generation Z employee respondents through saturated sampling technique. Data collection was conducted using a Likert scale questionnaire, then analyzed using SPSS version 27.0 with multiple linear regression technique. The results indicate that work culture has a positive and significant effect on Generation Z employee performance with t value 15.220 > t table 2.017 and significance 0.001 < 0.05. Conversely, employee retention partially has no significant effect on performance with t value -0.401 < t table 2.017 and significance 0.690 > 0.05. However, simultaneously both variables have a significant effect with F value 151.858 > F table 3.21 and determination coefficient of 87.3%. These findings indicate that strong work culture becomes the dominant factor in improving performance, while retention strategies need to be adjusted to the unique characteristics of Generation Z who prioritize work meaningfulness and flexibility. This research provides practical contributions for management in designing adaptive HR policies toward the needs of younger generation.